Interventions for chronic palmoplantar pustulosis: abridged Cochrane systematic review and GRADE assessments. (19th November 2020) - Obeid, G.; Do, G.; Kirby, L.; Hughes, C.; Sbidian, E.; Le Cleach, L.
Summary: Background: Palmoplantar pustulosis (PPP) is a chronic inflammatory disease in which sterile and relapsing pustules appear on the palms and soles. Objectives: To assess the effects of interventions for chronic PPP to induce and maintain complete remission. Methods: We searched for randomized controlled trials (RCTs), including people with PPP or chronic palmoplantar pustular psoriasis, in the Cochrane Skin Specialised Register, CENTRAL, MEDLINE, Embase, LILACS and eight trials registers up to July 2020. Study selection, data extraction and risk‐of‐bias assessment were carried out independently by two review authors. Certainty of evidence was assessed using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) method. Results: We included 37 RCTs (1663 participants, 76% women, mean age 50 years). Mean treatment duration was 11 weeks. Topical vitamin D derivative may be more effective than placebo in achieving clearance [risk ratio (RR) 7·83, 95% confidence interval (CI) 1·85–33·12; low‐certainty evidence from two trials]. Concerning biological therapies, there was little or no difference between etanercept and placebo in achieving clearance (low‐certainty evidence from one trial), ustekinumab is less effective than placebo in reducing severity (low‐certainty evidence from one trial), and guselkumab (RR 2·88, 95% CI 1·24–6·69) and secukinumab (RR 1·55, 95% CI 1·02–2·35) are probably better in reducing disease severity (moderate‐certainty evidence from two and one trial(s), respectively) but may cause more serious adverse events than placebo. Conclusions: Evidence is lacking for or against major chronic PPP treatments. Risk of bias and imprecision limit our confidence in the results. Abstract : What is already known about this topic? Palmoplantar pustulosis is a chronic inflammatory dermatosis that affects the hands and feet, and has a major impact on patients' quality of life. A Cochrane review published in 2006 concluded that there is no effective treatment and suggested that the standards of study design and reporting need to be improved to allow patients and clinicians to assess the effectiveness of treatments available. What does this study add? Evidence is still lacking for commonly used treatments such as topical corticosteroids, phototherapy, acitretin, methotrexate and ciclosporin. A topical vitamin D derivative may be more effective than placebo in achieving clearance in the short term (low‐certainty evidence). Secukinumab and guselkumab may be superior to placebo in reducing severity (moderate‐certainty evidence) than placebo but not ustekinumab (moderate‐certainty evidence). Linked Comment: Feldman and Huang. Br J Dermatol 2021; 184 :990 .